2020
DOI: 10.3390/en13133473
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Park and Ride System—A Case Study Based on the City of Cracow (Poland)

Abstract: The park and ride (P&R) parking type is usually located near peripheral public transport stops. These parking places are dedicated to people who, after leaving their vehicle in the parking, continue their journey to the city center using some form of public transport such as bus, metro, rail or tram systems. This article aims to examine the features associated with P&R parking locations in use in Cracow (Poland). The analysis included the number of entries and exits to and from parking during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…As for Sustainable Urban Public Transport (SUPT), it is also necessary to mention all the organisational and infrastructural measures aimed at limiting individual mobility in favour of public transport. Such solutions include, e.g., Park&Ride car parks [61][62][63][64][65] or Bike&Ride facilities [66][67][68]. The Bike&Ride solution is very often supported by municipalities that set up a public system of bike rentals as part of a Bike-Sharing System (BSS) [69][70][71][72]; it is more and more often also supplemented by an Electric Scooter Sharing system [73,74].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for Sustainable Urban Public Transport (SUPT), it is also necessary to mention all the organisational and infrastructural measures aimed at limiting individual mobility in favour of public transport. Such solutions include, e.g., Park&Ride car parks [61][62][63][64][65] or Bike&Ride facilities [66][67][68]. The Bike&Ride solution is very often supported by municipalities that set up a public system of bike rentals as part of a Bike-Sharing System (BSS) [69][70][71][72]; it is more and more often also supplemented by an Electric Scooter Sharing system [73,74].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers concerned about this issue have made several proposals to local governments to mitigate these problems. The majority of approaches have been a complete switch from private vehicles to a more friendly transport mode (e.g., pedestrians, bicycles, public transport) [18][19][20]. However, an alternative should also exist for inhabitants who own a private vehicle and live outside the urban area, and have limited or no connection to public transport services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Erdogan et al (2020) [22] proposed a maintenance decision support approach for PT systems in Istanbul, particularly for rapid transit bus systems, to eliminate the risks arising from related failures. Macioszek et al (2020) [23] examined the features associated with park and ride parking locations in Cracow and indicated that such park and ride systems are conducive to the development of PT in cities.…”
Section: Public Transportationmentioning
confidence: 99%